The Benefit Principles of Istibdāl on Wakaf Objects - Moh Mujibur Rohman (Jurnal Mahkamah : Kajian Ilmu Hukum Dan Hukum Islam, 2021)
The concept of waqf in fiqh is Islamic philanthropy in the form of amal Jariyah which requires the eternal characteristics of the object given. However, with the development of the era of waqf objects, it will be reduced mainly in property waqf. So that in order to keep the waqf objects productive, istibdāl is carried out in order to remain productive on the basis of mashlahah. To find the mashlahah principles in istibdāl, the author conducted a research of the boundaries of the mashlahah by al-Būthi. This research would not be far from the formulation of the problem that the author intended to find the answer; 1) what is the concept of istibdāl in fiqh and Indonesian representation? 2) What is the procedure for istibdāl waqf in the context of Indonesian waqf fiqh?; 3) How is the construction of mashlahah principles in istibdāl waqf practice based on dhawābithal-mashlahah al-Būthi? The research conducted was a normative research (doctrina), where the data used were secondary sources (not in the field) in the form of books of fiqh and legislation. From the data obtained, the authors conducted a descriptive analysis. The results showed that the permissibility of istibdāl waqf based on the mashlahah principle that must be fulfilled, that is, it must be in a state of dharurah, for urgent religious purposes, for the general public, there is an inadequacy, through the agreement of wāqif and nazhir, replaced at least with the same, the object of waqf is examined with involving figures and several elements of society as well as following the provisions of the Shari'ah and applicable laws.